2008
DOI: 10.1016/j.hrtlng.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Legionella community-acquired pneumonia (CAP) presenting with spontaneous bilateral pneumothoraces

Abstract: Legionnaires' disease is a common cause of non-zoonotic atypical community-acquired pneumonia (CAP). Legionnaires' disease has varied manifestations but may be diagnosed clinically on the basis of its characteristic pattern of extra-organ involvement. In a patient with non-zoonotic CAP, the clinical and laboratory features in a patient with CAP pointing to the diagnosis of Legionnaires' disease include relative bradycardia, mental confusion/ encephalopathy, loose stools/diarrhea, abdominal pain, mild/transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Hyponatremia occurs frequently in legionellosis 1, 6, 7, 8, 9, 10. Renal and hepatic dysfunction, elevated creatinine phosphokinase, thrombocytopenia, and leukocytosis are considered the common laboratory abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyponatremia occurs frequently in legionellosis 1, 6, 7, 8, 9, 10. Renal and hepatic dysfunction, elevated creatinine phosphokinase, thrombocytopenia, and leukocytosis are considered the common laboratory abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in cases of LP, respiratory symptoms such as cough and sputum are not prominent at first. Hyponatremia occurs frequently in legionellosis . Renal and hepatic dysfunction, elevated creatinine phosphokinase, thrombocytopenia, and leukocytosis are considered the common laboratory abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…167 Pneumothorax is an unusual feature of other types of CAP. 168 Pneumothorax is associated with certain types of pneumonia such as Pneumocystis carinii pneumonia, 169 and other causes of ARDS, especially in those requiring mechanical ventilation. 170 Exact rates are difficult to compare across studies, but rates as high as 49% in the pre-lung protective ventilation era have been reported.…”
Section: Imagingmentioning
confidence: 99%
“…Other clues not evident in this patient include hyponatremia (up to 50%), hypophosphatemia, increased CK, increased LDH, and relative bradycardia. [13][14][15][16][17] The rapidly progressive pneumonic consolidation in the patient was fairly typical, but nonspecific. Typical features include: focal infiltrates initially with contiguous spread to other lobes and bilaterally.…”
Section: Clinical Manifestations Of Legionella Pneumoniamentioning
confidence: 99%